Santri Leadership Patterns in Organizing in Islamic Union Islamic Boarding School (PERSIS) Bangil - Irfandi Amiruddin; Nurdyansyah Nurdyansyah; Taufik Churahman (Proceedings of The ICECRS, 2020)
Santri leadership patterns (people studying the teachings of Islam in Islamic boarding schools) in organizing are essential. The effectiveness of the activities of a pesantren related to santri is very much determined from the leadership pattern of the santri in the existing organization at the pesantren. So this study aims to determine the leadership style of students in a good pattern. Leadership is an attempt by someone to recognize and motivate their members to carry out a process to achieve the goals carried in a group or organization. The leader is functioned to formulate structural objectives and processes, ensure the integrity of the members, solve joint problems and follow up on the results of the evaluation. The organization itself is a unity of several people formed to achieve certain goals together. Organizational success depends on 4 things: (1) Planning, (2) Arrangement, (3) Reporting and (4) Supervision. This study uses a qualitative method that is collecting data in the form of words and understanding of the observations. This type of research is descriptive, the research serves to describe the pattern of leadership of students in organizing in the Islamic Union Islamic School (PERSIS) Bangil. From the results of the study, the santri leadership pattern in organizing in the PERSIS pesantren is a democratic leadership pattern, namely leadership that makes members as a team, deliberates on decisions and conveys work tasks in control and supervision. And this democratic leadership is oriented to faith and piety, good character and role models from the Prophet Muhammad.